1992
DOI: 10.1056/nejm199203193261203
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Fluconazole or Amphotericin B to Prevent Relapse of Cryptococcal Meningitis in Patients with the Acquired Immunodeficiency Syndrome

Abstract: Fluconazole taken by mouth is superior to weekly intravenous therapy with amphotericin B to prevent relapse in patients with AIDS-associated cryptococcal meningitis after primary treatment with amphotericin B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
5

Year Published

1993
1993
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(107 citation statements)
references
References 15 publications
0
102
0
5
Order By: Relevance
“…However, there were more relapses among subjects receiving the triple combination after they had been switched to itraconazole alone. The results of other studies (162,171) have suggested that relapse rates among subjects with HIV-associated cryptococcal meningitis are higher with itraconazole as a secondary prophylaxis than with fluconazole. It should also be noted that the dose of amphotericin B used in this study was less than that recommended in Infectious Diseases Society of America guidelines (172).…”
Section: Neoformans (I) In Vitro Datamentioning
confidence: 96%
“…However, there were more relapses among subjects receiving the triple combination after they had been switched to itraconazole alone. The results of other studies (162,171) have suggested that relapse rates among subjects with HIV-associated cryptococcal meningitis are higher with itraconazole as a secondary prophylaxis than with fluconazole. It should also be noted that the dose of amphotericin B used in this study was less than that recommended in Infectious Diseases Society of America guidelines (172).…”
Section: Neoformans (I) In Vitro Datamentioning
confidence: 96%
“…However, an infection may occur along with T-cell defects or following a CD4-lymphocyte-depleting therapy. D-AmB (0.7-1 mg/kg) plus 5-flucytosine (100 mg/kg) for 2 weeks followed by maintenance therapy with fluconazole 400 mg/ day for 10 weeks is the recommended antifungal treatment of cryptococcal meningitis in HIV-infected patients (see Table 4) (AI) [5,8,38,84,95]. Data about AmB lipid formulations are limited.…”
Section: Cryptococcus Neoformans Infectionsmentioning
confidence: 99%
“…Treatment by fluconazole of invasive infections due to various fungi has been a significant advance in antimicrobial chemotherapy (1,19,21). Its efficacy in treating cryptococcal and coccidioidal meningitis (2,3,5,14,22,23) is well established in clinical studies.In acute AIDS-associated cryptococcal meningitis fluconazole was shown to be as effective as amphotericin B (23) and more so in preventing relapse (3,22). However, use of fluconazole for treatment of this disease remains controversial (6,20,24), and the optimal dose remains uncertain.…”
mentioning
confidence: 99%